Pengaruh Model Pembelajaran Kooperatif Tipe Inside Outside Circle Berbantuan Media Audio Visual terhadap Kemampuan Berpikir Kritis Siswa SMP dalam Pembelajaran Matematika - Nessa Ovia Qulsum; Yahfizham Yahfizham; Suci Dahlya Narpila (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
One of the factors that causes low critical thinking skills of students is the use of inappropriate learning models in the learning process. The learning process has an important role in developing students' critical thinking skills. One of the learning models that is considered effective in improving students' critical thinking skills is the Inside Outside Circle model. So this study aims to determine the Effect of the Inside Outside Circle Cooperative Learning Model Assisted by Audio Visual Media on the Critical Thinking Skills of Junior High School Students in Mathematics Learning. The research method used is quantitative descriptive using the quasi-experimental method. The results of this study obtained the Independent sample t-test test showing that the significance of 0.024 at the significance level α = 0.05, the two-sided p significance level of 0.024, which means less than 0.05, then H_a is accepted and H_0 is rejected, which means there is a statistically significant effect of the Inside Outside Circle cooperative learning model assisted by audiovisual media on critical thinking skills.